Pengaruh Pelatihan Pliometrik Rasio 1:3 Dan 1:7 Terhadap Vo2 Max Atlet Panjat Tebing - Ida Bagus Laras; I Ketut Yoda; Luh Putu Tuti Ariani (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This research aims to determine the effect of pliometric training with a ratio of 1:3 and 1:7 on VO2 max ability in terms of leg muscle strength in rock climbing athletes. This research is a quantitative study with a quasi-experiment. The design in this study used a 2x2 factorial treatment by level design. The results showed: (1) there is a difference in VO2 max ability between rock climbing athletes who follow the plyomoterik model with a ratio of 1:3 and 1:7 (2) there is an interaction between plyomoterik training and leg muscle strength; (3) there is a difference in VO2 max ability between athletes who follow plyomoterik training with a ratio of 1: 3 and 1:7 ratios in rock climbing athletes who have strong leg muscle strength; (4) there is a difference in VO2 max ability between athletes who follow plyomoterik training with a ratio of 1:3 and a ratio of 1:7 in rock climbing athletes who have weak leg muscle strength.